Effect of 3D printing raster angle on reversible thermo-responsive composites using PLA/paper bilayer. (31st August 2020) - Shin, Sanghun; So, Hongyun
Abstract: In this study, an efficient fabrication method to realize a reversible thermo-responsive composite (TRC) and the effect of raster angle were investigated. For the facile fabrication of reversible TRCs, polylactic acid and commercial printing paper were used to generate a polymer/paper bilayer. Using the fused deposition modeling method of three-dimensional printing, three types of TRCs were fabricated and compared depending on the printing angle condition. Above the glass transition temperature, the polymer is relaxed, allowing straightening by the constraining paper layer; subsequently, it recovers its initial shape during cooling. Because the deposited filament arrays shrank in the longitudinal direction and expanded in another direction during heating, the raster angle was considered for better actuating performance. Thus, horizontal-type TRCs exhibited a greater range of average actuating performance compared with vertical-type TRCs (up to ∼24.7% increase in changing rate). Hence, this study supports a rapid, low-cost, and efficient fabrication method for soft robotics applications, including smart devices, grippers, and actuators.